Dermoscopic and clinical features of head and neck melanoma - Fatma Pelin Cengiz; Abdurrahman Bugra Cengiz; Nazan Emiroglu; Ela Comert; Rainer Hofmann Wellenhof (Sociedade Brasileira de Dermatologia, 2015)
AbstractBACKGROUND:The dermoscopic criteria of extrafacial melanomas are well-known.OBJECTIVE:To determine the frequency of dermatoscopic findings in head and neck melanomas (HNM) and to assess the distinguishing dermoscopic criteria of facial and extrafacial melanoma.METHODS:This observational study included 108 patients with HNM (63% male, mean age 64 years). Participants underwent individual dermoscopic imaging of clinically melanoma. All lesions were excised, and histopathological examination was performed on all specimens.RESULTS:Drawing on histopathological analysis, lentigo maligna melanoma or lentigo maligna was diagnosed in 60 lesions, superficial spreading melanoma in 18, nodular in 10, desmoplastic in 8, superficial spreading melanoma in situ in 12. The most frequent location for head and neck melanoma was the cheek (60 patients, 55.6%). Eight prominent dermatoscopic features were observed in facial melanoma: annular-granular pattern (18%); rhomboidal structures (29%); pseudonetwork (29%); asymmetrical, pigmented, follicular openings (51%); obliterated hair follicles (8%); red rhomboidal structures (18%); increased density of the vascular network (32%); scar-like depigmentation (59%).CONCLUSIONS:HNM has specific dermoscopic features, and classical extrafacial dermoscopic rules are less useful for diagnosis of facial melanoma. In our study, further characteristic dermatoscopic findings were detected in facial melanoma such as low frequencies of irregular dots, 2 or fewer colors in lesions, the presence of pseudonetwork, increased density of the vascular network, red rhomboidal structures, in addition to dermatoscopic findings of extrafacial melanoma. Thus, it is concluded that the prediction and identification of HNM may be evident with the help of these signs.